Understanding game application development : with Xamarin. Forms and ASP.NET - Durano, Vincent Maverick S. (Apress, 2019)
Learn to build a simple data-driven mobile game application using the power of Xamarin. Forms, ASP.NET, the Web API, and SignalR with this short book. --